Emissions, Fate and Transport of Persistent Organic Pollutants to the Arctic in a Changing Global Climate - Wohrnschimmel, Henry; MacLeod, Matthew; Hungerbühler, Konrad (Environmental Science & Technology, 2013)
ISSN:0013-936X ISSN:1520-5851